2012
DOI: 10.1111/jfpp.12061
|View full text |Cite
|
Sign up to set email alerts
|

Nisin Z-Producing Lactococcus lactis Subsp. Lactis  GYl32 Isolated from Boza

Abstract: In this study, bacteriocin‐producing Lactococcus lactis subsp. lactis GYL32 strain was isolated from Boza. The GYL32 strain inhibited not only related strains but also gram‐positive bacteria, such as Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus. The antimicrobial substance was inactivated after treatment with proteinase K and α‐chymotrypsin but not other enzymes. Bacteriocin remained active after 2 h of incubation at pH 2–11. It was stable to heat after treatment at 100C for 20 min. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 49 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…Downstream the NisZ gene cluster of L. cremoris WA2-67, two transposases showing homology with the lactococcal insertion sequence IS981 [68] were identified, which together with the sucrose operon constitutes a large nisin-sucrose conjugative transposon (Tn5276) [69]. NisZ-producing L. lactis strains are highly widespread in nature and have been isolated from several sources, including the intestine of the marine fish olive flounder (Paralichthys olivaceus) [70], fermented foods such as cheese [71], dahi (homemade fermented milk) [72], kimchi (Korean fermented vegetables) [73], nham (traditional Thai fermented sausage) [74], boza (cereal-based fermented beverage) [75], rice noodles [76], bean sprouts [77] and human stools [78]. Among the other known nisin variants, nisin F is the only one produced by a L. lactis strain of fish origin, namely freshwater catfish (Clarias gariepinus) [79].…”
Section: Discussionmentioning
confidence: 99%
“…Downstream the NisZ gene cluster of L. cremoris WA2-67, two transposases showing homology with the lactococcal insertion sequence IS981 [68] were identified, which together with the sucrose operon constitutes a large nisin-sucrose conjugative transposon (Tn5276) [69]. NisZ-producing L. lactis strains are highly widespread in nature and have been isolated from several sources, including the intestine of the marine fish olive flounder (Paralichthys olivaceus) [70], fermented foods such as cheese [71], dahi (homemade fermented milk) [72], kimchi (Korean fermented vegetables) [73], nham (traditional Thai fermented sausage) [74], boza (cereal-based fermented beverage) [75], rice noodles [76], bean sprouts [77] and human stools [78]. Among the other known nisin variants, nisin F is the only one produced by a L. lactis strain of fish origin, namely freshwater catfish (Clarias gariepinus) [79].…”
Section: Discussionmentioning
confidence: 99%
“…Under these experimental conditions, the size was larger than that of Lactococcus nisin-producer strains, suggesting that extra molecules could associate into a larger complex compound. An early study showed that L. lactis strain GLY32 isolated from boza produced a bacteriocin of 6.7 kDa [ 48 ]. Likewise, in this study, the molecular size of commercial nisin was about 10 kDa on SDS-PAGE.…”
Section: Resultsmentioning
confidence: 99%
“…Known bacteriocinogenic strain Lactococcus lactis subsp. lactis GYL32 was used as the positive control (Koral and Tuncer, 2014). These LAB isolates and the standard bacteriocin producer strain were grown in de Man, Rogosa and Sharpe (MRS) broth or on MRS agar at 30 °C under unaerobic conditions.…”
Section: Bacterial Strainsmentioning
confidence: 99%